2019
DOI: 10.23989/gerontologia.78039
|View full text |Cite
|
Sign up to set email alerts
|

Folkhälsans seniorboende och aktivt åldrande – BoAktiv-studien

Abstract: Syftet med denna enkät-studien är att utreda samband mellan aktivt åldrande, gemenskap och delaktighet hos åldringar som bor i seniorhus. Utöver detta syftar forskningen till att producera beskrivande information om hälsa och välmående hos åldringar i seniorhus. Målgruppen var självständigt boende i Folkhälsans seniorhus. Största delen av respondenterna var över 80 år gamla, kvinnor, svenskspråkiga och bodde ensamma. De mest aktiva seniorerna hade bättre hälsorelaterad livskvalitet samt mindre symptom av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
2
1
Order By: Relevance
“…Unlike we assumed, senior houses’ proximity of amenities, recreational spaces, and public transport (Jolanki 2021; Tyvimaa, 2011) seemed to be insufficient to enhance the residents’ possibilities for various activity. In addition, although it was recently reported that active aging correlates with sense of community and social participation (Lahti et al, 2019; Sirén et al, 2023), the findings of this study suggest that senior housing residents, living in a communal environment with organized activities, did not perceive equal levels of active aging compared to community-dwelling older people. This is likely due to poorer function of senior housing residents (Lahti et al, 2021) and may reflect the “in-between” nature of senior houses when living in a private dwelling is no longer feasible but there is still potential for leading an independent life.…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…Unlike we assumed, senior houses’ proximity of amenities, recreational spaces, and public transport (Jolanki 2021; Tyvimaa, 2011) seemed to be insufficient to enhance the residents’ possibilities for various activity. In addition, although it was recently reported that active aging correlates with sense of community and social participation (Lahti et al, 2019; Sirén et al, 2023), the findings of this study suggest that senior housing residents, living in a communal environment with organized activities, did not perceive equal levels of active aging compared to community-dwelling older people. This is likely due to poorer function of senior housing residents (Lahti et al, 2021) and may reflect the “in-between” nature of senior houses when living in a private dwelling is no longer feasible but there is still potential for leading an independent life.…”
Section: Discussioncontrasting
confidence: 88%
“…We utilized data from two studies: the BoAktiv senior housing survey (Lahti et al, 2019) and the Active Aging—Resilience and External Support as Modifiers of the Disablement Outcome (AGNES) study (Rantanen et al, 2018). The BoAktiv data included people residing independently in Folkhälsan owned private senior houses, who were over 55 years of age, and Finnish- or Swedish-speaking.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation